Four pioneers on play. (2nd December 2021) - Willis, Richard
Abstract : Steiner, Kant, Dewey and Froebel are introduced in this article in regards to their lessons on play in early childhood settings. The four theorists are compared, outlining some of the common threads interwoven between them.